1994
DOI: 10.1177/0265407594114003
|View full text |Cite
|
Sign up to set email alerts
|

Masculinity, Femininity and Relationship Satisfaction: The Mediating Role of Interpersonal Competence

Abstract: The purpose of this study was to examine more fully the relationship between masculinity, femininity and satisfaction among dating couples. A multivariate causal model was developed and tested to assess Ickes' (1985) conceptual model of gender-role influences on relationship satisfaction. Dating couples ( N = 174) completed the Personal Attributes Questionnaire, the Interpersonal Competence Questionnaire and the Relationship Satisfaction Scale. Results indicated that for both males and females, relationship sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 16 publications
3
33
0
1
Order By: Relevance
“…Generally, assertive behaviours are considered to be masculine qualities, while responsive behaviours are considered to be feminine qualities [47] [48]. Moreover, assertive individuals are considered extroverted and powerful whereas responsive individuals are considered trustworthy and sociable [49] [50]. Responsive instructors are also viewed as being sensitive and understanding [51], being verbally receptive to students [52] and contributing to perceived students' learning and satisfaction [52] [53] [54].…”
Section: Socio-communicative Stylementioning
confidence: 99%
“…Generally, assertive behaviours are considered to be masculine qualities, while responsive behaviours are considered to be feminine qualities [47] [48]. Moreover, assertive individuals are considered extroverted and powerful whereas responsive individuals are considered trustworthy and sociable [49] [50]. Responsive instructors are also viewed as being sensitive and understanding [51], being verbally receptive to students [52] and contributing to perceived students' learning and satisfaction [52] [53] [54].…”
Section: Socio-communicative Stylementioning
confidence: 99%
“…It is important, for example, to romantic relationships (e.g., Frisbie, Fitzpatrick, Feng, & Crawford, 2000;Lamke, Sollie, Durbin & Fitzpatrick, 1994), professional success (e.g., Riggio & Taylor, 2000), parenting (e.g., BartleHaring & Sabatelli, 1997), popularity and coping in high school and youth (Buhrmester, Furman, Wittenberg, & Reis, 1988;Cairns, Cairns, & Neckerman, 1989), and self-esteem (Buhrmester et al, 1988). Crucially, impaired interpersonal competence associates with vulnerability to stress and negative life events (Cummings et al, 2013;Segrin, 2001), loneliness (DiTommaso, Brannen-McNulty, Ross, & Burgess, 2003), and, perhaps more importantly, psychopathology (Segrin, 1990(Segrin, , 1993Skodol et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers use the term of instrumental vs expressive qualities instead of masculine vs feminine traits and therefore in this view, masculine individuals are expected to show instrumental behaviors and feminine individuals are expected to show expressive behaviors (Lamke, Sollie, Durbin, & Fitzpatrick, 1994). However, some research findings about sex roles in Turkey have not confirmed these expectations in terms of instrumental vs. expressive qualities.…”
Section: Sex Role Orientationmentioning
confidence: 99%